Pelatihan Pembuatan Hand Sanitizer Perasan Buah Jeruk Nipis Bagi Ibu-Ibu Di Perumahan 1 Rt 24 Bentiring Kota Bengkulu - Siska, Jumiati; Yul , Fadlul Amdhi; Pratama , Benny Agung (Universitas Dehasen Bengkulu, 2019)
Hand sanitizer (hand antiseptic) is a health product that can kill germs instantly without using water, can be used anytime and anywhere, for example after handling money, before eating, after going to the toilet and after taking out the trash. The purpose of this service activity is to produce a health product that can be utilized both for oneself, for the family and for the surrounding community. The method used is in the form of lectures containing explanations of material and the practice of making hand sanitizers. The result of this community service is the participants' understanding of the manufacture of hand sanitizers from natural materials and their functions.